2007
DOI: 10.3402/ljm.v2i4.4728
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin sensitivity of Staphylococcus aureus isolates from hospital patients in Karachi, Pakistan

Abstract: Methicillin-resistant Staphylococcus aureus (S. aureus) (MRSA), resistant to all antibiotics including Vancomycin, has been reported in Japan, USA, Canada and Brazil. Hence, the main objective of this study was to evaluate the possible presence of Vancomycin resistant or intermediate S.aureus in Karachi. A total of 850 clinical isolates were collected from two civil hospitals in the city between February 2006 and January 2007. They were identified using standard bacteriological methods.Sensitivity to recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
9
4
Order By: Relevance
“…The present study encountered one VRSA strain (0.8%) with VA MIC 32µg/ml. Many studies encountered VRSA strains at higher frequencies than that reported in our study; Saderi et al 51 reported that 3.5% of SA isolates were VRSA and Hakim et al 52 reported VISA (13%). On the other hand, Dhanalakshmi, et al 24 reported that no VISA or VRSA were found among MRSA strains.…”
Section: Discussioncontrasting
confidence: 48%
“…The present study encountered one VRSA strain (0.8%) with VA MIC 32µg/ml. Many studies encountered VRSA strains at higher frequencies than that reported in our study; Saderi et al 51 reported that 3.5% of SA isolates were VRSA and Hakim et al 52 reported VISA (13%). On the other hand, Dhanalakshmi, et al 24 reported that no VISA or VRSA were found among MRSA strains.…”
Section: Discussioncontrasting
confidence: 48%
“…The MIC profile revealed 7 (8.97 %) MRSA isolates as VISA. A previous study conducted at Pakistan also reported 13 % frequency of VISA using MIC by E test (Hakim et al 2007 ). In the current study, we observed 15.84 % inducible clindamycin resistance in MRSA isolates which is in line with other studies (Yilmaz et al 2007 ; Maninder et al 2013 ).…”
Section: Discussionmentioning
confidence: 87%
“…MIC 50 MIC 90 0.19 to 3 µg/ml 0.75 µg/ml 1.5 µg/ml strains were detected in a study carried out in King Edward Medical College Lahore in 2004. In the year 2007, 13% VISA strains were detected from 2 civil hospitals of Karachi but no VRSA strain was detected (Mehmood et al, 2007;Bukhari et al, 2004;Hakim et al, 2007). Regional studies show following VISA incidence, 3.3% in Srinagar Kashmir 2003, 6% in India 2007and 7.5% in Iran 2008(Assadullah et al, 2003Mehdinejad et al, 2008;Horieh et al, 2005).…”
Section: Rangementioning
confidence: 99%